2023
DOI: 10.1186/s12974-023-02986-5
|View full text |Cite
|
Sign up to set email alerts
|

27-hydroxycholesterol causes cognitive deficits by disturbing Th17/Treg balance and the related immune responses in mild cognitive impairment patients and C57BL/6J mice

Tao Wang,
Wenjing Feng,
Mengwei Ju
et al.

Abstract: Background Cognitive impairment is associated with dysregulated immune responses. Emerging evidence indicates that Th17 cells and their characteristic cytokine-IL-17 are receiving growing interest in the pathogenesis of cognitive decline. Here, we focus on the involvement of Th17 cells in mild cognitive impairment (MCI) and the possible mechanism of cholesterol metabolite-27-hydroxycholesterol (27-OHC). Methods 100 individuals were recruited into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…27-hydroxycholesterol (27-OHC) is a cholesterol metabolite that was found to be increased in brains of subjects with mild cognitive impairment (MCI), a prodromal condition of AD. Mice treated with 27-OHC had increased SAA in their brains, which was associated with altered Th17/Treg balance that was dependent on RORγt [ 94 ]. It has also been shown that SAA1 overexpression in an AD mouse model that forms amyloid beta plaques results in worse plaque deposition, gliosis, and memory impairment [ 73 ].…”
Section: Evidence For the Involvement Of Saa Proteins In Cns Diseasesmentioning
confidence: 99%
“…27-hydroxycholesterol (27-OHC) is a cholesterol metabolite that was found to be increased in brains of subjects with mild cognitive impairment (MCI), a prodromal condition of AD. Mice treated with 27-OHC had increased SAA in their brains, which was associated with altered Th17/Treg balance that was dependent on RORγt [ 94 ]. It has also been shown that SAA1 overexpression in an AD mouse model that forms amyloid beta plaques results in worse plaque deposition, gliosis, and memory impairment [ 73 ].…”
Section: Evidence For the Involvement Of Saa Proteins In Cns Diseasesmentioning
confidence: 99%